(untitled) (Interdisciplinary Studies Journal, 2024)
This article investigates the perception of students majoring in Rural Education/Natural Sciences in Piauí regarding the teaching of Chemistry, through the administration of a questionnaire via Google Forms. The research follows a qualitative, descriptive approach, with a case study as the investigative method. The majority of students believe that the content is easy, but they recognize a weak foundation in high school, where classes were disconnected from real-life applications and lacked hands-on experiments. In higher education, active teaching methodologies are well-received, allowing for connections with everyday life and more meaningful learning. Nevertheless, many still consider a change in the teaching of Chemistry at Licenciatura em Educação do campo/Ciências da Natureza – Piauí (LEDOC/CN-PI) to be necessary. The study highlights the importance of a contextualized and inclusive approach, aiming to educate teachers who are committed and aligned with the reality of students in rural communities. This will promote relevant learning and contribute to sustainable development and the appreciation of local identities."